2019
DOI: 10.1111/pai.13034
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of drug‐induced anaphylaxis in children: An EAACI position paper

Abstract: Drug hypersensitivity reactions (DHR) constitute a major and common public health problem, particularly in children. One of the most severe manifestations of DHR is anaphylaxis, which might be associated with a life‐threatening risk. During those past decades, anaphylaxis has received particularly a lot of attention and international consensus guidelines have been recently published. Whilst drug‐induced anaphylaxis is more commonly reported in adulthood, less is known about the role of drugs in pediatric anaph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(94 citation statements)
references
References 73 publications
1
81
1
3
Order By: Relevance
“…However, in a retrospective study, STs have demonstrated a PPV of 99.4%, indicating their usefulness, before DPT . Large multicentre studies, to evaluate the real diagnostic predictive values of ST, are needed …”
Section: Diagnosismentioning
confidence: 98%
See 2 more Smart Citations
“…However, in a retrospective study, STs have demonstrated a PPV of 99.4%, indicating their usefulness, before DPT . Large multicentre studies, to evaluate the real diagnostic predictive values of ST, are needed …”
Section: Diagnosismentioning
confidence: 98%
“…85 Large multicentre studies, to evaluate the real diagnostic predictive values of ST, are needed. 86 In the case of NIR, due to the potential risk of triggering a severe reaction, the diagnostic procedure starts with a patch test and if negative, IDTs, although recent studies suggest the performance of IDTs with no need of a previous patch testing. 87,88 Unfortunately, the real diagnostic value of STs for SCARs is unknown, as confirmatory DPTs cannot be performed for ethical reasons due to the risk of inducing a severe reaction when reintroducing the culprit drug.…”
Section: In Vivo Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Also often presenting with a skin rash, drug allergy is the theme of the second review: Marina Atanaskovic-Markovic et al have in the frame of an EAACI task force reviewed the diagnosis and management of drug-induced anaphylaxis. 2 The topic of the third review relates to another major focus of the journal, primary immunodeficiencies, with Parisa Amirifar et al 3 reviewing ataxia-telangiectasia.…”
Section: Local Rhinitis Needs Allergen-challenges For Diagnosis Latementioning
confidence: 99%
“…Educational publications open the issue: In the first, Hagen Ott reviews the various clinical conditions related to erythroderma in neonates and infants; allergists are used to linking this clinical sign to atopic dermatitis, but nevertheless should be well aware of other, less frequent diagnosis . Also often presenting with a skin rash, drug allergy is the theme of the second review: Marina Atanaskovic‐Markovic et al have in the frame of an EAACI task force reviewed the diagnosis and management of drug‐induced anaphylaxis . The topic of the third review relates to another major focus of the journal, primary immunodeficiencies, with Parisa Amirifar et al reviewing ataxia‐telangiectasia.…”
mentioning
confidence: 99%